Management of Farmer Producer Companies (FPCs) - Issues and Challenges - Rao, A. Naga Durga; Lakshmi, S. B. Ramya; Darekar, Ashwini (Journal of Agricultural Extension Management, 2022)
The concept of FPOs or collectivization of farmers is not a new thing to the Indian Agriculture Sector. We experienced cooperative movement for more than 100 years. However, the cooperative could not achieve greater success on account of inherent limitations. Hence, a new generation of FPOs registered under Companies Act came up in the year 2002 on the recommendations of Prof. Y K Alagh Committee. Farmer Producer Company (FPC) a legal institution, registered under Company Amendment Act 2002 (1 of 2003) or also called Producer Company Act 2002 is emerging as the most effective means of Farmer Producer Organization (FPO) to cater to the needs of farmers at the grassroots level. This paper explains the concept of FPCs, their salient features, objectives, legal provisions along with steps to form and run FPCs. It also explains the powers and functions of Board Members, CEOs and other officer bearers and describes the status of FPCs in India with the schemes of Govt. of India which support FPCs in the country.